PELATIHAN DASAR PENGGUNAAN MICROSOFT POWERPOINT BAGI GURU SD KADILANGU BAKI SUKOHARJO - Maria Atik Sunarti Ekowati; Sri Wening; Kristyana Dananti (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
Advances in science and technology have an impact on the state's demands that the success of the education system be anticipated by encouraging the state to progress more quickly. Formal and non-formal education is used to assist teachers in achieving the level of mastery of the science and technology taught to students. The implementation of the Tri Darma of Higher Education, one of which is community service, with the theme: Basic Training on Using Microsoft Powerpoint for Teachers at Kadilangu Baki Sukoharjo Elementary School aims to provide mastery of Power Point for teachers so that it can be transformed into students in providing learning by making interesting presentations. After the PowerPoint training, the participants experienced an increase in understanding, because previously they did not understand PowerPoint tools, how to insert text, images, sound and video and set effects and backgrounds with PowerPoint, but now it has increased above 65%.